ETODOLAC DOSAGE FORMULATION AND PROCESS FOR PREPARING THE SAME - Kaur, Gaganjot; Upendra Kumar Jain, (International Journal of Psychosocial Rehabilitation, 2019)
Etodolac belongs to the class of “non-steroidal anti-inflammatory class of drugs” (NSAIDs) with anti-inflammatory, analgesic and anti-pyretic effects. At lower doses, NSAIDs provide analgesic properties, while higher doses are needed to produce anti-inflammatory action. The treatment of osteoarthritis, rheumatoid arthritis and relatively extreme post-surgical pain relief is effective with Etodolac. Etodolac was used in the treatment of ankylosing spondylitis, post-operative pain (dental, orthopedic or obstetric surgery) and in non surgical pain (tendonitis, lower back pain, gout or sports injury). The goal of the research is to include a bilayer tablet formulation of etodoloac for rapid uptake and eventual rapid onset of action to relieve acute pain. Using various excipients, the extended discharge comprises is prepared by wet granulation. The formulation comprises of effective amount of active ingredient etodolac or salts thereof in combination with compressible powder, superdisintegrant and effervescent agent.